ASSESSING THE IMPACT OF GLYCAEMIC CONTROL ON LIVER FUNCTION IN TYPE 2 DIABETES: A CROSS-SECTIONAL RETROSPECTIVE ANALYSIS OF LIVER CHEMISTRIES - Ndaba, Londeka Nontobeko; Jaya , Ziningi Nobuhle; Thembane, Nokukhanya (Student’s Journal of Health Research Africa, 2025)
Objective This study investigates the relationship between liver biomarkers and glycaemic control in Type 2 Diabetes Mellitus (T2DM) patients at King Edward Hospital, KwaZulu-Natal, South Africa. Methods A retrospective, cross-sectional study was conducted on 80 patients diagnosed with T2DM. Data collected included gender distribution, age range, glycaemic control (HbA1c, fasting glucose, and random glucose), and liver function markers (bilirubin, ALT, AST, and GGT). The study period ranged from June 2023 to December 2023. Patients were evaluated for glycaemic control and liver biomarkers, and statistical analysis was performed to explore correlations between these factors. Results The majority of patients (57.5%) were aged 46-65, with an emerging trend of younger patients being diagnosed with T2DM. A significant gender disparity was observed, with females comprising 83.8% of the study population. All participants exhibited HbA1c levels in the diabetic range (≥6.5%), indicating poor glycaemic control. A notable proportion of patients showed elevated liver enzymes: 35.7% had mildly elevated ALT levels, 29.6% had elevated AST levels, and 75.2% had abnormal GGT levels. Positive and significant correlations were found between HbA1c and liver enzymes: HbA1c and ALT (r = 0.43, p < 0.01), HbA1c and AST (r = 0.51, p < 0.01), and HbA1c and GGT (r = 0.61, p < 0.01). These findings suggest that poor glycaemic control is strongly associated with liver dysfunction. Conclusion The results indicate a strong association between poor glycaemic control and elevated liver enzymes in T2DM patients, highlighting the need for comprehensive management strategies targeting both glycaemic control and liver health. Regular monitoring of liver biomarkers should be considered to facilitate early detection of liver dysfunction, potentially preventing severe liver-related complications. Recommendations Regular liver function monitoring should be integrated into diabetes management, particularly for the early detection of conditions like NAFLD. Improving glycaemic control is crucial to mitigate liver-related complications.